The political economy of the world trading system : from GATT to WTO - Hoekman, Bernard M.; Kostecki, Michel M. (Oxford ; New York : Oxford University Press, 1995)
The World Trade Organization is likely to be a major international organization for the foreseeable future. This volume, the first full-length study of the WTO and GATT from the viewpoint of public choice and political economy, details the mechanics of the multilateral trading system that emerged from the Uruguay Round of GATT. The authors, who were involved in the negotiations of the Uruguay Round, explain why WTO rules are phrased the way they are, the successes and failures of WTO and GATT, and how business, industrial associations and political lobbies influence the multilateral trading system.
Includes bibliographical references and index.
lje 24/08/16
Loans
Keywords: International trade; International economic relations; Tariff